Effect of Local Counterpart Funding Delay on Procurement of Donor Funded Projects - Kotey, Samuel (2015)
A thesis submitted to the Department of Building Technology in partial fulfilment of the requirements for the degree of Master of Philosophy (MPHIL) in Procurement Management.